Kontribusi Pendidikan Islam Menuju Indonesia Maju - Usri Usri (IAIN PAREPARE, 2019)
This study aims to discuss about the contribution of Education in particular Islamic Education in welcoming Indonesia forward. The theme becomes urgent to be studied to explore further about Islamic education in the history of the Indonesian people who have trodden more than half a century of age. The method used in this research is literature study. Based on the results of the study found the active role of the old order government, the new order and reform through several strategic policies to foster Islamic education in Indonesia. The position of Islamic education as an educational institution, as subjects and values of Islamic Education contained in the National Education System. Until the contribution of Islamic Education in the development of quality human resources towards Advanced Indonesia. Islamic education is part of the Indonesian nation and the progress of the Indonesian people has a strong relationship with the dynamics of Islamic education.